The Portuguese generic medicines market: A policy analysis. - Simoens S (Pharmacy Practice, 2009)
Objectives: This study aims to conduct a descriptive analysis of the policy environment surrounding the generic medicines retail market in Portugal. The policy analysis focuses on supply-side measures (i.e. market access, pricing, reference-pricing and reimbursement of generic medicines) and demand-side measures (i.e. incentives for physicians to prescribe, for pharmacists to dispense and for patients to use generic medicines).Methods: The policy analysis was based on an international literature review. Also, a simulation exercise was carried out to compute potential savings from substituting generic for originator medicines in Portugal using IMS Health data.Results: Portugal has developed a successful generic medicines market by increasing reimbursement of generic medicines (until October 2005), by introducing a reference-pricing system, by encouraging physicians to prescribe by international non-proprietary name (INN), and by allowing generic substitution by pharmacists. However, the development of the generic medicines market has been hindered by the existence of copies, pricing regulation, certain features of the reference-pricing system, weak incentives for physicians to prescribe generic medicines and a financial disincentive for pharmacists to dispense generic medicines. Increased generic substitution would be expected to reduce public expenditure on originator medicines by 45%.Conclusions: The development of the Portuguese generic medicines market has mainly been fuelled by supply-side measures. To support the further expansion of the market, policy makers need to strengthen demand-side measures inciting physicians to prescribe, pharmacists to dispense and patients to use generic medicines.